The Visual Elements of Computer-based Language Assessment: Aspects and Effects - Sarab Al-Ani (Studies in Applied Linguistics & TESOL, 2012)
The advent of computers and computer assisted technologies has certainly influenced many aspects of our personal and professional lives. The field of second language education is no exception, where such technologies first exerted their influence on conventional teaching methods, and from there moved onto methods of testing in second language acquisition. This transition from the “world of paper” to that of a computer screen and the associated technologies is arguably one of the most significant changes witnessed in second language education since the invention of the printing press. One of the questions that many studies tried to answer in regard to this change was: what effect do the visual elements of computer-based language tests have on test-takers?